NOCTUID MOTHS (LEPIDOPTERA, NOCTUIDAE, NOCTUINAE) OF ISLANDS OF OF THE NORTH-WESTERN CASPIAN SEA - A. G. Abdurakhmanov (Юг России: экология, развитие)
This article is devoted to the short review of noctuid moths (NOCTUINAE). There is a species staff presented here as well as characteristics of each species of this subfamily, that were found out both in our and our colleagues collections of complex researches of biological diversity.